Analysis of Aedes Aegypti Larval Density on The Potential Transmission of Dengue Fever - Maria Nuraeni (Eduvest - Journal of Universal Studies, 2024)
Dengue hemorrhagic fever (DHF) is caused by the dengue virus transmitted through the Aedes aegypti mosquito. DHF remains a health problem in Indonesia. Based on data from the Ministry of Health, there were 184 cases of the disease in 2022, an increase of 94.8% compared to 2021, which had 73,518 cases. According to the Central Statistics Agency of South Sumatra Province, the number of DHF cases in South Sumatra was 2,854 cases, with the highest number in the city of Palembang at 908 cases. This condition requires serious attention. The aim of this study is to analyze the potential transmission of DHF based on entomological evidence in the Sukarami district of Palembang. The method used in the research is a cross-sectional study conducted in December 2023, involving 92 households in the Sukarami sub-district, with a total of 552 containers. The survey results of larval identification under a microscope showed a Larval Free Index of 45.7%, a Container Index of Aedes aegypti larvae of 56.0%, a house index of 73.9%, and a Breteau index of 152.2%. The results of entomological indices indicate a high density of DHF vector mosquitoes Aedes aegypti, which means that this area has a high risk of DHF transmission, thus requiring the control of Aedes aegypti larvae and the eradication of DHF. breeding sites for the vector.